2008
DOI: 10.1103/physreve.77.041606
|View full text |Cite
|
Sign up to set email alerts
|

Slip boundary conditions for shear flow of polymer melts past atomically flat surfaces

Abstract: Molecular dynamics simulations are carried out to investigate the dynamic behavior of the slip length in thin polymer films confined between atomically smooth thermal surfaces. For weak wall-fluid interactions, the shear rate dependence of the slip length acquires a distinct local minimum followed by a rapid growth at higher shear rates. With increasing fluid density, the position of the local minimum is shifted to lower shear rates. We found that the ratio of the shear viscosity to the slip length, which defi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 48 publications
11
64
0
Order By: Relevance
“…The MD results for flat crystalline walls confirm previous findings [30] that the slip length goes through a local minimum at low shear rates and then increases rapidly at higher shear rates. For periodically corrugated surfaces and wetting conditions, …”
supporting
confidence: 81%
See 1 more Smart Citation
“…The MD results for flat crystalline walls confirm previous findings [30] that the slip length goes through a local minimum at low shear rates and then increases rapidly at higher shear rates. For periodically corrugated surfaces and wetting conditions, …”
supporting
confidence: 81%
“…The slip length was calculated by the linear extrapolation of the fluid velocity profile to zero with respect to a reference plane, which is located 0.5 σ away from the fcc lattice plane [27,30]. Figure 4 shows the rate dependence of the slip length in the same range of shear rates as in Fig.…”
Section: MD Results For Flat Wallsmentioning
confidence: 99%
“…Even though we intend to disassociate the dynamic and structural behaviors from the thermal effect by enforcing a uniform fluid temperature, as the shear rate gets higher, the fluid temperature inside the system starts to deviate from the set temperature of T = 1.1 ε/k B . This has also been observed in other studies [24,40,41]. To examine how the fluid temperature alters as a result of the shearing, a local fluid temperature (kinetic temperature) as a function of z for each slab of the simulation cell is computed by using the kinetic energy:…”
Section: Velocity Profiles Vs Shear Ratesmentioning
confidence: 62%
“…He also found that the shear-rate dependence weakens as the wall stiffness decreases [17]. Niavarani and Priezjev [26] also investigated the shear-rate dependence of slip in polymer melts and observed that as shear increases, the slip length has a local minimum before rapidly increasing.…”
Section: Introductionmentioning
confidence: 94%